2017
DOI: 10.1016/j.epsl.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Microscale characterization of rupture nucleation unravels precursors to faulting in rocks

Abstract: 16Precursory signals, manifestations of microscale damage that precedes dynamic faulting, are key 17 to earthquake forecasting and risk mitigation. Detections of precursors have primarily relied on 18 measurements performed using sensors installed at some distance away from the rupture area in 19 (1991). However, the dynamic imaging presented here allows understanding 3D porosity 129 development, crack anisotropy and the role of heterogeneities in general at the scale of a whole 130 sample. 131 Results 132

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 33 publications
5
62
0
Order By: Relevance
“…Optical microscopy (Moore & Lockner, ; Tapponnier & Brace, ), scanning electron microscopy (Brace et al, ), laser scanning confocal microscopy (Fredrich et al, ), and acoustic emissions (Lockner et al, ) have revealed some of the microstructural origins of precursors prior to macroscopic failure. Complementary to these techniques, dynamic X‐ray microtomography coupled with triaxial load cell is a unique tool for imaging the microstructure of crustal rocks that are subjected to deformation (e.g., Renard et al, ; Renard, Mcbeck, et al, ; Renard, Weiss, et al, ; Iglauer & Lebedev, ). This technique provides three‐dimensional microstructural information on damage distribution as failure is approached and is complementary to other imaging techniques such as acoustic emissions (e.g., Renard, McBeck, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Optical microscopy (Moore & Lockner, ; Tapponnier & Brace, ), scanning electron microscopy (Brace et al, ), laser scanning confocal microscopy (Fredrich et al, ), and acoustic emissions (Lockner et al, ) have revealed some of the microstructural origins of precursors prior to macroscopic failure. Complementary to these techniques, dynamic X‐ray microtomography coupled with triaxial load cell is a unique tool for imaging the microstructure of crustal rocks that are subjected to deformation (e.g., Renard et al, ; Renard, Mcbeck, et al, ; Renard, Weiss, et al, ; Iglauer & Lebedev, ). This technique provides three‐dimensional microstructural information on damage distribution as failure is approached and is complementary to other imaging techniques such as acoustic emissions (e.g., Renard, McBeck, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in time‐resolved three‐dimensional microtomography imaging (e.g., Renard et al, , ) and three‐dimensional digital volume correlation (DVC) analysis (e.g., Tudisco et al, ) enable in situ investigations of deformation processes via quantification of shear and volumetric strains within rocks and other materials. In this study, we aim to better understand fracture development within mechanically anisotropic shale and characterize the transition from diffuse deformation to strain localization and the propagation of and slip along shear fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Similarities in the mode of fault development are observed for low (5 MPa) and intermediate (15 MPa) effective pressures: Pervasive tensile cracking initially affects the samples; subsequent interlinking reflects the formation crack clusters, which then coalesce to form the final shear plane. At relatively high effective pressure (30 MPa), cracks parallel to the applied main compressive stress ( σ 1 ) mostly form along a well‐developed plane; then rapid linkage localizes the fault along a finite‐size process zone (Reches & Lockner, ; Renard et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution BSE images allowed us to study fault initiation over a significant area within samples deformed under a range of effective pressures (from 5 to 30 MPa; Figure 4). ), cracks parallel to the applied main compressive stress ( 1 ) mostly form along a well-developed plane; then rapid linkage localizes the fault along a finite-size process zone (Reches & Lockner, 1994;Renard et al, 2017).…”
Section: Discussionmentioning
confidence: 99%